The haunting of Hillside School - Gregory, Kristiana; Faricy, Patrick (New York : Scholastic, 2008)
Cousins Jeff, David, and Claire investigate the possible haunting of their schoolhouse.
"Little Apple"--Spine.
RL3.
007-010.
Accelerated Reader AR
Keywords: Cousins -- Juvenile fiction; School buildings -- Juvenile fiction; Schools -- Juvenile fiction; Ghost stories; Mystery fiction